Regional features of management of patients diagnosed with chronic gastritis at the inpatient and outpatient-polyclinic stages. Brief pharmacoeconomic analysis - E. N. Chicherina; M. A. Matasova; A. S. Knyazeva (Лечащий Врач)
Complex study of management strategy for patients with chronic gastritis was done at pre-clinical and clinical stages in real clinical practice. The schemes of treatment applied in hospital and those recommended for outpatient application were shown, their functional and economic efficiency was estimated.